2001
DOI: 10.1042/bst0290345
|View full text |Cite
|
Sign up to set email alerts
|

Role of reactive oxygen species in cell signalling pathways

Abstract: Reactive oxygen species (ROS) were originally thought to only be released by phagocytic cells during their role in host defence. It is now clear that ROS have a cell signalling role in many biological systems, both in animals and in plants. ROS induce programmed cell death or necrosis, induce or suppress the expression of many genes, and activate cell signalling cascades, such as those involving mitogen-activated protein kinases.(1) 20, + NADPH -+ 20,-' + NADP+ + H+ (2) AbstractThe ability of medium from y-irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
297
0
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 632 publications
(309 citation statements)
references
References 9 publications
2
297
0
10
Order By: Relevance
“…The mechanisms of induction of stress response genes are similar among various organisms examined. Similarities in stress-induced changes in gene expression have been observed for a variety of stressors (3,(6)(7)(8). Some that have been studied in detail include radiation, thermal shock, pathogenic infections, anaerobiosis, trauma, photostress, physical wounding, oxidative stress, water stress, and heavy metals.…”
Section: Gene Responsesmentioning
confidence: 79%
“…The mechanisms of induction of stress response genes are similar among various organisms examined. Similarities in stress-induced changes in gene expression have been observed for a variety of stressors (3,(6)(7)(8). Some that have been studied in detail include radiation, thermal shock, pathogenic infections, anaerobiosis, trauma, photostress, physical wounding, oxidative stress, water stress, and heavy metals.…”
Section: Gene Responsesmentioning
confidence: 79%
“…It has been observed that physiological levels of ROS are necessary for normal regulation of cell growth and development (Hancock et al 2001). The MnSOD is an important enzyme involved in protection against ROS.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 is considered to be an important reactive oxidant species and causes cell death via either apoptosis or necrosis. 24 HEK293 cells remained intact following exposure for 24 and 72 h to OA at concentrations of 20 and 80 μmol L À1 , indicating that OA does not cause DNA damage in kidney cell lines. Similar results were obtained for the MDBK cells (results not shown).…”
Section: Cell Culture Studiesmentioning
confidence: 98%